Pengembangan Fitur Notifikasi WhatsApp sebagai Pendukung Sistem CRM dalam Optimalisasi Layanan Pelanggan - Melfika Sheylawatin; Moh. Anshori Aris Widya (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
Communication management and task coordination are crucial elements in the operational performance of the garment manufacturing industry. Tariz Konveksi, a medium-sized garment business in Jombang, still relies on conventional communication systems, resulting in miscommunication between departments, production delays, and decreased customer satisfaction. This study aims to design and develop a web-based task management system integrated with WhatsApp Notifications to improve operational effectiveness and customer service based on Customer Relationship Management (CRM) principles. The research employed the Research and Development (R&D) method using the ADDIE approach, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through interviews, observations, and direct documentation. The system was developed using Node.js, MySQL, and the WhatsApp API. System testing was conducted through black-box testing and pre- and post-implementation surveys. The results indicate that the proposed system is capable of delivering real-time automated notifications to employees regarding assigned tasks and deadlines, as well as providing customers with updates on their order status. The implementation of the system is expected to reduce communication errors, shorten manual response times, and enhance customer satisfaction. This research contributes by providing a model for integrating WhatsApp Notifications into a task management system that can be adopted by medium-scale garment industries as a digital communication solution based on CRM principles.